Assessing Indonesia and Malaysia’s Legal Responsiveness to Domestic Violence Victims within Islamic Law Framework - Nuroniyah, Wardah; Al Azkiya, Mohammad Azka; Wahid, Abdul; Labib Shodiq, Fatimah Lubabiyah; Maula, Bani Syarif (Al-Manahij: Jurnal Kajian Hukum Islam, 2025)
This study presents a comparative analysis of Indonesia and Malaysia’s legal frameworks for protecting victims of domestic violence through the lens of Islamic legal principles. It examines both substantive and procedural dimensions in light of maqāṣid al-sharī‘ah, which emphasize the preservation of life (ḥifẓ al-nafs), dignity (ḥifẓ al-‘ird), and family integrity (ḥifẓ al-nasl). Indonesia’s Law No. 23 of 2004 provides broad substantive protection by recognizing various forms of violence physical, psychological, sexual, and economic and extending safeguards to domestic workers. This inclusivity aligns with the Islamic principle of ‘adl (justice) and the duty to uphold human dignity, though weak coordination and limited law enforcement training hinder procedural implementation. In contrast, Malaysia’s Domestic Violence Act 1994 demonstrates stronger procedural responsiveness, particularly in issuing protection orders and promoting inter-agency cooperation. While its narrower scope excludes domestic workers, it reflects dar’ al-mafāsid (prevention of harm) through timely intervention. Malaysia’s dual legal system also integrates Islamic values into judicial practice. The study concludes that Indonesia excels in substantive inclusivity, while Malaysia demonstrates procedural strength. A hybrid model combining Indonesia’s normative scope with Malaysia’s procedural efficiency would better fulfill the Shariah’s holistic objectives of justice and protection.